Figure Skating Injuries
A. Boot-related injuries i. Malleolar Bursitis ii. Pump Bumps iii. Tibialis Anterior and Extensor Hallux Tendonitis iv. Achilles Tendonitis v. Other Tendonitis vi. Other Problems B. Prevention of boot-related injuries C. The ankle instability syndrome of the ice skater